2019
DOI: 10.1039/c9qm00081j
|View full text |Cite
|
Sign up to set email alerts
|

A fluorescence and photoactivity dual-activatable prodrug with self-synergistic magnification of the anticancer effect

Abstract: A hydroxycamptothecin prodrug is developed, which can self-report the drug distribution and achieve self-synergistic anticancer efficacy through oxidation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 59 publications
(63 reference statements)
0
11
0
Order By: Relevance
“…Phototheranostics, as a powerful cancer treatment protocol with the integrated functionalities of light-driven diagnostic imaging In addition, recent advances have demonstrated that AIEgens can also serve as phototheranostic agents for multimodal imaging-guided synergistic therapy through rational molecular design, benefiting from the inherent capabilities of AIEgens as an extraordinary template for subtly regulating the balance between radiative and nonradiative decays. [24][25][26][27][28] It is known that the photophysical properties of AIEgens are vital for the phototheranostic applications according to the Jablonski diagram. [2] An AIEgen absorbs the photon energy along with the transition of its electrons from the ground state to higher energy states followed by the energy dissipation process which generally involves three pathways corresponding to different phototheranostic functions: (1) fluorescence imaging/diagnosis through radiative decay pathway; (2) photothermal therapy (PTT) and photoacoustic imaging via thermal deactivation process (nonradiative decay pathway); (3) through intersystem crossing (ISC) for phosphorescence afterglow imaging and/or generation of cytotoxic reactive oxygen species (ROS) for photodynamic therapy (PDT).…”
Section: Introductionmentioning
confidence: 99%
“…Phototheranostics, as a powerful cancer treatment protocol with the integrated functionalities of light-driven diagnostic imaging In addition, recent advances have demonstrated that AIEgens can also serve as phototheranostic agents for multimodal imaging-guided synergistic therapy through rational molecular design, benefiting from the inherent capabilities of AIEgens as an extraordinary template for subtly regulating the balance between radiative and nonradiative decays. [24][25][26][27][28] It is known that the photophysical properties of AIEgens are vital for the phototheranostic applications according to the Jablonski diagram. [2] An AIEgen absorbs the photon energy along with the transition of its electrons from the ground state to higher energy states followed by the energy dissipation process which generally involves three pathways corresponding to different phototheranostic functions: (1) fluorescence imaging/diagnosis through radiative decay pathway; (2) photothermal therapy (PTT) and photoacoustic imaging via thermal deactivation process (nonradiative decay pathway); (3) through intersystem crossing (ISC) for phosphorescence afterglow imaging and/or generation of cytotoxic reactive oxygen species (ROS) for photodynamic therapy (PDT).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, regardless of the extent to which the ligand ratio is elevated on the NP surfaces, the cellular uptake will not be increased (Kibria et al, 2011;Takara et al, 2012;Mei et al, 2014). To overcome this barrier and promote the cellular uptake efficacy, a dual-ligand targeted drug delivery system with the aim of reinforcing the tumor-targeting specificity has arisen (Jang et al, 2015;Mezghrani et al, 2015;Yang et al, 2015;Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To improve the efficacy of cancer chemotherapeutics, in 2019, Ding and Zheng reported a fluorescence and photoactivity dual‐activatable prodrug 28a , which was composed of a 4‐dimethylamino‐2′‐hydroxychalcone fluorogen with AIE characteristics, a disulfide bond, and the anticancer drug hydroxycamptothecin. [ 95 ] Utilizing an amphiphilic copolymer as the encapsulation carrier, 28a nanoparticles (about 126 nm in size) in aqueous solution were obtained, and these were favorable for in vivo applications. Upon addition of GSH, the disulfide bonds were cleaved, followed by release of active anticancer drug 28d and compound 28e , which could emit brighter AIE fluorescence and generate ROS under light irradiation for synergistic treatment of tumors.…”
Section: Aiegens For Analysis Of Small Moleculesmentioning
confidence: 99%